Cold war paradise : settlement, culture, and identity-making among U.S. Americans in Costa Rica, 1945-1980 - Shragai, Atalia (University of Nebraska Press, 2022)
"Atalia Shragai examines the motivations for immigration, patterns of movement, settlements, and processes of identity-making among U.S. Americans in Costa Rica from post-World War II to the late 1970s"--